Does Going Digital Matter In Communicating Corporate Social Responsibility To The Public? A Systematic Review Approach - Adanlawo, Eyitayo Francis; Chaka, Mpho (Journal of Ecohumanism, 2025)
The way companies communicate their CSR commitment is critical for organisational success and legitimacy, particularly in the age of new media. Corporate websites, social media accounts, and other interactive platforms are just a few of the ways that businesses are embracing the new digital technologies and communicating their policies and responsible initiatives. To comprehend the justification for utilising digital media to communicate corporate social responsibility (CSR) activities, digital media theory was adopted to aid comprehension of the changing dynamic between society and technology. The results from systematic reviews have indicated that stakeholder engagement and the perceived usability and ease of use of online media for CSR disclosures are important for business development. More so, the ability and benefits of new media to have two-way, participatory interactions with stakeholders, and thereby create additional value for firms and stakeholders, makes it essential. These findings suggest that companies should prioritize transparency and interactivity in their digital communications to foster trust among stakeholders. By effectively harnessing online platforms, organizations can enhance their reputation and demonstrate a genuine commitment to social responsibility, ultimately leading to stronger relationships with their audience. This study concludes by suggesting that CSR communication is more effective when it is easily accessible online.